Лингвистическая интерпретация политического события в современном коммуникативном пространстве - Moiseenko, Lilia V. (Mundo Eslavo, 2015)
The article deals with different interpretations of a communicative event in Mass Media. The applied interpretative method makes it possible to single out discursive strategies used by politicians to present their version of reality as the only true one. The processuality of the sense as one of the characteristics of the text helps to present a political text as a system of senses and use discursive strategies to create a social reality through media reality.